Effects of piper betle extract supplementation diet as a natural antibiotic growth promoter (NAGP) to kelah (Tor tambroides) - Mohd Yusof, Hanan; Othman, Ahmad Baihaqi; Nik Yusoff, Nik Haiha; Jaapar, Muhd Zudaidy; Abdullah, Azila; Nawi, Mohd Firdaus; Mansor, Nur Nazifah (Department of Fisheries Malaysia, 2022)
The present study was conducted to evaluate the potential of Piper betle extract as a herbal product as a feed additive and a natural antibiotic growth promoter (NAGP) toward kelah (Tor sp.) on antimicrobial activity and growth performance. In this study, for antimicrobial activity, several concentration levels of Piper betle extract were tested to observe the optimum dosage for bacterial inactivation of Aeromonas hydrophila obtained from the kelah specimen. Then, in the growth study, two treatment methods were used, which were once a month (S1) and fortnightly (S2) feedings of a diet treated with 100 ppm Piper betle extract, with a non-treated Piper betle extract diet serving as a control (C). All treatments were conducted in duplicate and the fish were stocked at 10 fish m-2 in 3MT tanks. Fishes were fed ad libitum, twice daily. The results showed the optimal dosage for Piper betle extract was identified at 100 ppm with a significant different (P > 0.05) in the size of the Aeromonas hydrophila bacterial inhibitory zone, with diameters of 18.7 ± 0.6 mm. While at 182 days of growth study, the results show that the best growth performance of kelah according to body weight gain (BWG) was treatment S2 with 131.9 ± 9.1 %, followed by S1 and control at 104.8 ± 10.2 % and 84.2 ± 9.5 %, with a significant difference (P < 0.05). While the S2 treatment significantly showed the best feed conversion ratio (FCR) compared to the S1 and control treatments, with 3.57 ± 0.17, 4.27 ± 1.13, and 5.02 ± 0.49, respectively. Overall, there was no significant difference in survival rate among all treatments in this study. Thus, the results suggest that Piper betle can be considered as a NAGP in the diet at the optimum dose of 100 ppm, with fortnightly application as the best feeding regime for kelah culture.